Laparoscopic anti-reflux surgery for the treatment of idiopathic pulmonary fibrosis (WRAP-IPF): a multicentre, randomised, controlled phase 2 trial. Issue 9 (September 2018) - Raghu, Ganesh; Pellegrini, Carlos A; Yow, Eric; Flaherty, Kevin R; Meyer, Keith; Noth, Imre; Scholand, Mary Beth; Cello, John; Ho, Lawrence A; Pipavath, Sudhakar; Lee, Joyce S; Lin, Jules; et al.
Summary: Background: Abnormal acid gastro-oesophageal reflux (GER) is hypothesised to play a role in progression of idiopathic pulmonary fibrosis (IPF). We aimed to determine whether treatment of abnormal acid GER with laparoscopic anti-reflux surgery reduces the rate of disease progression. Methods: The WRAP-IPF trial was a randomised controlled trial of laparoscopic anti-reflux surgery in patients with IPF and abnormal acid GER recruited from six academic centres in the USA. We enrolled patients with IPF, abnormal acid GER (DeMeester score of ≥14·7; measured by 24-h pH monitoring) and preserved forced vital capacity (FVC). We excluded patients with a FVC below 50% predicted, a FEV1 /FVC ratio of less than 0·65, a history of acute respiratory illness in the past 12 weeks, a body-mass index greater than 35, and known severe pulmonary hypertension. Concomitant therapy with nintedanib and pirfenidone was allowed. The primary endpoint was change in FVC from randomisation to week 48, in the intention-to-treat population with mixed-effects models for repeated measures. This trial is registered withClinicalTrials.gov, numberNCT01982968 . Findings: Between June 1, 2014, and Sept 30, 2016, we screened 72 patients and randomly assigned 58 patients to receive surgery (n=29) or no surgery (n=29). 27 patients in the surgery group and 20 patients in the no surgery group had an FVC measurement at 48 weeks (p=0·041). Intention-to-treat analysis adjusted for baseline anti-fibrotic use demonstrated the adjusted rate of change in FVC over 48 weeks was −0·05 L (95% CI −0·15 to 0·05) in the surgery group and −0·13 L (−0·23 to −0·02) in the non-surgery group (p=0·28). Acute exacerbation, respiratory-related hospitalisation, and death was less common in the surgery group without statistical significance. Dysphagia (eight [29%] of 28) and abdominal distention (four [14%] of 28) were the most common adverse events after surgery. There was one death in the surgery group and four deaths in the non-surgery group. Interpretation: Laparoscopic anti-reflux surgery in patients with IPF and abnormal acid GER is safe and well tolerated. A larger, well powered, randomised controlled study of anti-reflux surgery is needed in this population. Funding: US National Institutes of Health National Heart, Lung and Blood Institute.